(untitled) (Discourse of Law and Administration, 2026)
The doctor’s liability is regulated depending on the method of establishing an employment relationship with him. In the event of damage caused by a doctor, the Labor Code specifies three ways in which the doctor may be held liable. One of the regulations indicates that the employer is responsible for the damage caused by the employee. In this case, a healthcare facility. However, the facility repairing the patient’s injury has the so-called recourse against the physician who caused the damage in question. The Labor Code also provides for three types of material liability of the employee: for damage caused by unintentional fault and for damage caused by intentional fault, as well as for damage resulting from the employee’s failure to account for the property entrusted with the obligation to return or account for it.